Inflammation and prostate cancer. (October 2008) - Vasto, Sonya; Carruba, Giuseppe; Candore, Giuseppina; Italiano, Emilio; Di Bona, Danilo; Caruso, Calogero
Prostate cancer remains a major health concern for the male population throughout the Western world. It is today widely accepted that inflammation has a role in many human cancers. In fact, inflammation is thought to incite carcinogenesis by causing cell and genome damage, promoting cellular turnover and creating a tissue microenvironment that can enhance cell replication, angiogenesis and tissue repair. Accordingly, there is a body of literature suggesting a link between chronic inflammation and prostate cancer, in which prostate inflammation may contribute to the promotion of prostate cancer development. On the other hand, high levels of endogenous gonadal steroids are considered as risk factors for prostate cancer. Interestingly, it is clear that elevation of estrogens in the presence of testosterone results in a prostate-specific inflammatory response. Thus, it is possible that early inflammatory events stimulated by sex hormones serve as a prerequisite for the onset of prostate cancer.